Evolution: a Journal of Nature: ciência, evolução e fundamentalismo nos estados unidos (1927-1938) - Henrique Rodrigues Caldeira (2018)
This study analyzes the magazine Evolution: a Journal of Nature, published between 1927 and 1938 in the United States, in order to understand its participation in the public controversy on the theme of evolution. In this context, evolution had become the subject of a wide and intense debate, mainly due to its presence in the growing national public education. For progressive reformers of American secondary schools, evolution was seen as the axis for the unification of biology, a discipline which should play an important role in the civic education of the new and turbulent industrial society. For the self-titled "fundamentalists," representatives of a growing conservative protestant movement, evolution would be identified as the root of all evil of secular modernity. This tension would culminate in dozens of laws against evolution teaching some of them approved by congress, others challenged in court prompting much public debate on the subject. Following this controversy in the pages of Evolution, an evolutionary publication, we investigate how it developed its opposition to the fundamentalist activism, how it represented the idea of evolution, and how it understood its own role in history. In order to do so, we analyze material e textual aspects of the journal, so as to situate it in its broader historical-scientific context and reflect on the complex relationship between science and society.